A Precisely‐Controlled Multichannel Phononic Crystal Resonant Cavity (Adv. Theory Simul. 12/2021). Issue 12 (7th December 2021) - Zhang, Xiaopeng; Jia, Zhiyuan; Luo, Yangjun; Wang, Yaguang; Liu, Pai; Kang, Zhan
Abstract : A Precisely‐Controlled Multichannel Phononic Crystal Resonant Cavity A novel multichannel PnC based energy‐harvesting conceptual device with high localization effect and high frequency resolution is reported in article number 2100250 by Luo and co‐workers. The configurations of PnC cavities are designed by the proposed two‐stage topology optimization strategy using the material‐field series‐expansion model. The cover depicts a resonant cavity device with five‐parallel‐channels where each channel can accurately capture the energy of incident wave at the respective frequency.